Attitudes toward concealed carry on campus: results from a nationwide survey of criminologists. Issue 3 (26th May 2020) - Hassett, Matthew R.; Kim, Bitna
ABSTRACT: A small but growing number of studies has explored the attitudes about this campus carry policy held by campus community members. The current study expands on the literature on this topic by examining criminologist attitudes. More specifically, this study aimed to investigate the level of support for permitting firearms on campus and to what degree do specific predictors impact criminologists' views towards the policy. Using survey data collected from a total of 1, 554 criminologists, we found that the criminologists in our sample were overwhelmingly opposed to the idea of permitting concealed carry on college campuses. Results showed that while criminologists' attitudes toward concealed carry on campus were generally negative, the attitudes varied depending on their university affiliation status and state campus policy, with faculty working in states where campus carry is prohibited reporting the strongest degree of opposition and graduate students in states where campus carry is permitted reporting the strongest support. Hierarchical multiple regression analyses also revealed that attitudes toward the policy could be partially predicted by prior socialization with firearms, fear of campus crime, and current campus safety measures. These results are discussed in terms of implications for policy and future research.